15% enhancement of the photocurrent at the maximum power point of a thin film solar cell. Issue 11 (18th September 2020) - Shekhar, Himanshu; Tessler, Nir
Abstract : A modulation doped region placed away from the charge generation region reduces recombination loss by enhancing the charge extraction. Abstract : Recent efficiency enhancement of organic solar cells has been achieved through material and chemical engineering of the chemistry and morphology of the donor–acceptor junction. Inducing band bending at the junction through ground state charge transfer between the donor and acceptor is an important route but realising it through chemical design is challenging. Here we demonstrate a device engineering approach to modify the junction's electronic structure improving the maximum power point (MPP) current by 50% and the current at 80% of the open-circuit voltage (0.8 V OC ) by 30%. We report modulation-doping of the hole transport layer while exploring the effect of the thin doped-layer distance from the junction. To avoid ambiguity in the interpretation of the results, we utilize a bi-layer structure and choose to insert the dopant into a wide band gap donor so as to avoid direct interaction with photogenerated excitons. Using a device model, we show that the doped-layer induces long range enhancement of the internal electric field, all the way between the p-type doped-layer and the cathode. Such enhancement is especially important at the MPP where the contact-induced internal electric field tends to diminish. In state of the art solar cells, the current at the MPP is at least 15% below the short-circuit current ( J SC ) suggesting that our method might induce improvement in such cells too (18% × 1.15 = 20.7%).